Exercício físico é eficaz para melhorar dor, mobilidade funcional e qualidade de vida de indivíduos com osteoartrose de quadril? Uma revisão sistemática com metanálise - Caduda, Suziany dos Santos (2023)
Randomized clinical trials with individuals with hip osteoarthritis (HO) has been published, however, there is no consensus in the literature regarding the effectiveness of exercise in OAQ on pain, functional mobility (FM) and quality of life (QoL) in these individuals and therefore some recommendations are based on the evidence related to the knee, or mixed populations. Thus, the objective of this review was to evaluate the effectiveness of physical exercise and its implications for pain, FM and QoL in individuals with isolated OAQ. This is a systematic review with meta-analysis, in which the search was carried out in the Pubmed, Embase, CINAHL, CENTRAL (Cochrane) and PEDro databases updated in August 2022. Randomized controlled trials with individuals (adults) with hip osteoarthritis were included treated with physical exercise (resistance, aerobic, mixed) compared with the control (exercise different from the intervention or no intervention). The risk of study bias (Cochrane tool – ROB 1) and the quality of certainty of evidence (GRADE) were analyzed. Study selection was performed by two independent reviewers and outcomes related to pain, physical function and quality of life were extracted. Seven studies (n=243) met the inclusion criteria and only four were included in the meta-analysis. Most studies showed an uncertain risk of bias. There was no significant difference between the mixed exercise versus no intervention groups in the meta-analysis, neither for pain (MD -0.47, 95%CI= - 1.36 to 0.42; p-value=0.30) nor for QoL (SMD 0.08, 95% CI = - 0.47 to 0.62; p = 0.20) in the short term, both with small effect sizes. Low-intensity resistance exercise showed a statistically significant difference in relation to high-intensity resistance exercise in terms of pain, with a mean effect size (MD 1.30, 95% CI= 0.32 to 2.28; p=0.009), but not for function, with a small effect size (MD -0.10, 95%CI= -0.20 to -0.00; p=0.05) in the short term. However, the evidence found in the present study ranges from very low to low quality and the effect size is not clinically relevant. Thus, new clinical trials with rigor and methodological quality should be carried out to investigate the effectiveness of physical exercise in individuals with OAQ and which is the most effective modality in pain, MF and QoL for future clinical decision-making.